Consensus on early detection of disease progression in patients with multiple sclerosis - Meca-Lallana, José E.; Casanova, Bonaventura; Rodríguez-Antigüedad, Alfredo; Eichau, Sara; Izquierdo, Guillermo; Durán, Carmen; Río, Jordi; Hernández, Miguel Ángel; Calles, Carmen; Prieto-González, José M.; Ara, José Ramón; Uría, Dionisio F.; et al. (Frontiers in Neurology, 2022)
Background: Early identification of the transition from relapsing-remitting multiple sclerosis (RRMS) to secondary progressive MS (SPMS) can be challenging for clinicians, as diagnostic criteria for SPMS are primarily based on physical disability and a holistic interpretation. Objective: To establish a consensus on patient monitoring to identify promptly disease progression and the most useful clinical and paraclinical variables for early identification of disease progression in MS. Methods: A RAND/UCLA Appropriateness Method was used to establish the level of agreement among a panel of 15 medical experts in MS. Eighty-three items were circulated to the experts for confidential rating of the grade of agreement and recommendation. Consensus was defined when ≥66% agreement or disagreement was achieved. Results: Consensus was reached in 73 out of 83 items (87.9%). The items addressed frequency of follow-up visits, definition of progression, identification of clinical, cognitive, and radiological assessments as variables of suspected or confirmed SPMS diagnosis, the need for more accurate assessment tools, and the use of promising molecular and imaging biomarkers to predict disease progression and/or diagnose SPMS. Conclusion: Consensus achieved on these topics could guide neurologists to identify earlier disease progression and to plan targeted clinical and therapeutic interventions during the earliest stages of SPMS.